Linguistic Landscape of Chałupki - Mrůzková, Kateřina (Mundus Slavicus I, 2025)
The first part of this article introducing the concept of the linguistic landscape, then focusing on the history of Chałupki, especially its connection with the Czech Republic. The second part of the article is devoted to empirical research. The subject of the empirical research are mainly the communicates in the Czech language that appeared in the village. The collected materials are divided into two cateogories – top-down and bottom-up signs. The space is also devoted to the analysis of the empirical materials collected by the author during field research conducted from March to August 2024.Článek vznikl v rámci řešení vědeckého projektu „Jazyková krajina na pozadí multietnicity česko-polského pohraničí / Linguistic Landscape in the Context of Multiethnicity in the Czech-Polish Borderland” (SGS10/FF/2024).